Dimensions of physical fitness evaluation procedures among police personnel: systematic literature review - Emmanuel, Fadero Oluwafemi; Omar Dev, Roxana Dev; Norjali Wazir, Mohd Rozilee Wazir (Human Resource Management Academic Research Society, 2023)
Being a police officer is a physically tasking occupation that requires much fortitude. The importance of having physically fit police officers cannot be emphasized. The research assessed the existing state of knowledge on the dimensions of physical fitness evaluation procedures among police personnel by conducting a complete literature review. The PRISMA principles were followed throughout the paper search and analysis. After examining electronic databases (Sport Discus, PubMed, Science Direct, and Scopus), 664 studies were retrieved. The chosen studies must include both male and female active police officers, be published in English between January and October 2022, and evaluate the participants' fitness levels. The quantitative synthesis comprised 9 studies with a total of 3275 male and female participants. The methodology of the physical fitness evaluations in all the studies was of high quality, less emphasis was placed on the health measures. The 2,400meter run is the most prevalent cardiovascular health test, followed by the sit-up, leg press, and push-up test, the vertical jump, the Illinois test, and body mass index. The amount number of push-ups an officer could accomplish, their handgrip strength, and their agility were found to correspond with their work performance. Due to the vast variety of fitness test dimensions and test selection procedures, standardization of fitness test protocols is required for accurate and meaningful comparability of findings. For future research on police fitness evaluation to be really unique, there is a need to further create a norm standard for various test batteries, primarily for the police population.